Pemberdayaan Masyarakat Desa Bihe, Kabupaten Gorontalo melalui Diversifikasi Kelapa Menjadi Virgin Coconut Oil dan Cocopeat - Novri Youla Kandowangko; Muchtar Ahmad; Mustamin Ibrahim; Febriyanti (Institut Pertanian Bogor, 2024)
Bihe Village is one of the villages in Asparaga District, Gorontalo Regency, which is a center for coconut production. The abundant potential of coconut plants has yet to be utilized optimally by the people of Bihe village. Coconuts are only produced as copra, or coconuts are sold whole, without processing. Coconut plants have many derivative products, such as virgin coconut oil (VCO) and coconut peat. This problem prompted the implementation of socialization, training, and assistance in making VCO and Cocopeat for the Bihe village community. The aim is to increase the community's insight and skills regarding the diversification of coconut products so that they can provide additional income, which can improve the economy in Bihe Village. The training method is the Participatory Action Research (PRA) method, which involves the active role of the Bihe village community. The stages carried out are analysis of the actual conditions of society, planning, action, observation, and reflection. This method is carried out to provide an understanding of a) the weaknesses they have, b) the community's desire to overcome their shortcomings and weaknesses, c) together with the community to develop strategies and methods to solve the problem, and d) help the community overcome, solve, and find a way out. Forty participants attended this training and mentoring. After implementing the empowerment program, the post-test results showed that 62.5% of the community gave an excellent assessment, and 37.5% gave a good assessment of the usefulness of this activity program. Furthermore, 72.5% of participants were motivated to open a new coconut commodity business.